Impact of ocean mixed layer depth on tropical cyclone characteristics: a numerical investigation - Zhang, Yalan; Han, Kaifeng; Sun, Yuan; Lin, Yanluan; Zhai, Panmao; Guo, Xinwen; Zhong, Wei (Frontiers in Marine Science, 2024)
The impact of upper-ocean temperature on tropical cyclone (TC) activity is an open issue. Compared to the attention devoted to the effect of sea-surface temperature (SST) on TC activities, much less is known about the effect of ocean mixed layer depth (OMLD) on TC activities, which is determined by the ocean temperature below the surface. In this study, a series of idealized numerical experiments were conducted to investigate the possible responses of TC activities to OMLD. It was found that while OMLD exerts a minor influence on TC track, it evidently affects TC intensity, size, and destructiveness before reaching a certain OMLD threshold (approximately 15 m). Once the OMLD exceeds the threshold, changes in TC intensity, size, and destructiveness become marginal with further increase in OMLD. The threshold of OMLD is largely determined by TC intensity, which in turn is dictated by surface wind speed. Specifically, before reaching the threshold of OMLD, the surface wind, namely TC-related surface wind, may bring the cold water from below the OMLD, and effectively decreases the upper ocean temperature (including the SST). As OMLD increases, the effect of surface wind on SST cooling gradually decreases, leading to an increase of SST below the TC. Subsequently, the SST increase leads to more surface enthalpy flux (SEF) input into the TC by increasing air-sea temperature and moisture differences. By altering TC's thermodynamic and dynamic structures, the increase of SEF eventually results in the increase of TC intensity and size, and thus its destructiveness.